(untitled) (Journal of Technology and Operations Management, 2018)
This paper identified factors of student acceptance in the sustainability of upcycling as well as analyzed student acceptance level in the sustainability of upcycling among students of a residential college in Universiti Utara Malaysia (INASIS Grantt). Using student survey-based method in a quantitative approach, this study distributed a set of questionnaires to gather primary data from targeted respondents. A total of 200 respondents were randomly distributed. Printed-out questionnaires were handed out, accompanied by an upcycled product that was built as a real-life product. Data were also collected through completed questionnaires through the use of the Internet. The items in the questionnaire were based on the sustainability of upcycling. The data were analyzed using Statistical Package for Social Science (SPSS) version 24. The results of the analysis showed a significant correlation between environmental, economic, and social with student acceptance. It was concluded that INASIS Grantt students accepted upcycling can be a new method on campus to create sustainable products that has the potential of reducing pollution while generating side income. An additional benefit includes reducing waste material at the landfill, when the student can use any recycled item to make some innovation that surely will give a lot of benefit and profit to those who want to make money.